Asymptotic behavior of discrete evolution families in Banach spaces. Issue 2 (25th January 2018) - Buşe, Constantin; Khan, Aftab; Nguyen, Lan T.; O'Regan, Donal; Rahmat, Gul
Abstract : Let X be a Banach space, be an operator-valued sequence and let be the discrete evolution family associated to In this paper we prove that the family is non-uniformly strongly stable (i.e. for every nonnegative integer m and every if and only if it is -approximative admissible, i.e. for every sequence in and every positive number there exists the sequence in satisfying such that the solution of the discrete Cauchy Problem belongs to Other types of asymptotic behavior of the family are also analyzed.